Antiplasmodial Chalcones Inhibit Sorbitol-Induced Hemolysis of Plasmodium falciparum-Infected Erythrocytes - Go, Mei-Lin (American Society for Microbiology, 2004)
A series of alkoxylated and hydroxylated chalcones previously reported to have antiplasmodial activities in vitro were investigated for their effects on the new permeation pathways induced by the malaria parasite in the host erythrocyte membrane. Of 21 compounds with good antiplasmodial activities (50% inhibitory concentrations [IC(50)s], ≤20 μM), 8 members were found to inhibit sorbitol-induced lysis of parasitized erythrocytes to a significant extent (≤40% of control values) at a concentration (10 μM) that was close to their antiplasmodial IC(50)s. Qualitative structure-activity analysis suggested that activity was governed to a greater extent by a substitution on ring B than on ring A of the chalcone template. Most of the active compounds had methoxy or dimethoxy groups on ring B. Considerable variety was permitted on ring A in terms of the electron-donating or -withdrawing property. Lipophilicity did not appear to be an important determinant for activity. Although they are not exceptionally potent as inhibitors (lowest IC(50), 1.9 μM), the chalcones compare favorably with other more potent inhibitors in terms of their selective toxicities against plasmodia and their neutral character.